2021
DOI: 10.1111/are.15205
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of partial replacement fish meal with poultry by‐products in practical diets of juvenile great sturgeon, Huso huso : Effects on growth performance, body composition, physiometabolic indices, digestibility and digestive enzymes

Abstract: Nowadays, sturgeon aquaculture is a rapidly growing industry in the world, and considerable attention has been paid to this practice in Iran (Kalbassi et al., 2013). The great sturgeon, Huso huso, is one of the valuable species owning to their meat and especially caviar, and hence, nutritional administration of sturgeon is necessary for aquaculture. Fish meal (FM) is the most important component of the diet in carnivore fish mainly owing to its high protein value, essential n-3 fatty acids, indispensable amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
1
4
0
2
Order By: Relevance
“…PBPM instead of FM as a protein source had no significant effects on muscle proximate composition of coho salmon. Similar results were reported in studies for grouper [48], Oreochromis niloticus [62], Pagrus pagrus [49], Sparus aurata [63], Tinca tinca [64], Lutjanus guttatus [65], Sparidentex hasta [11], Chanos chanos [66], yellow catfish [57], Siberian sturgeon (Acipenser baerii) [67], and great sturgeon (Huso huso) [68]. In comparison, Amirkolaie et al [46] reported that dry matter and fat content of Oncorhynchus mykiss fillets were reduced in the PBPM 100% replacement group, while water content increased with increasing levels of PBPM replacement.…”
Section: Discussionsupporting
confidence: 86%
“…PBPM instead of FM as a protein source had no significant effects on muscle proximate composition of coho salmon. Similar results were reported in studies for grouper [48], Oreochromis niloticus [62], Pagrus pagrus [49], Sparus aurata [63], Tinca tinca [64], Lutjanus guttatus [65], Sparidentex hasta [11], Chanos chanos [66], yellow catfish [57], Siberian sturgeon (Acipenser baerii) [67], and great sturgeon (Huso huso) [68]. In comparison, Amirkolaie et al [46] reported that dry matter and fat content of Oncorhynchus mykiss fillets were reduced in the PBPM 100% replacement group, while water content increased with increasing levels of PBPM replacement.…”
Section: Discussionsupporting
confidence: 86%
“…A further higher replacement level, 60%, reduced both weight gain and SGR. Similarly, the weight gain and SGR of juvenile great sturgeon ( Huso huso ) were markedly lower than other groups when more than 60% of fishmeal in the feed was replaced with PBM (Hassani et al, 2021). In hybrid striped bass ( Morone chrysops ♀ × M .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the weight gain and SGR of juvenile great sturgeon (Huso huso) were markedly lower than other groups when more than 60% of fishmeal in the feed was replaced with PBM (Hassani et al, 2021). In hybrid striped bass (Morone chrysops ♀ × M. saxatilis ♂), a limit between 35% and 70% replacement of fishmeal protein with TA B L E 9 Effects of fishmeal replacement by PBM on the muscle fatty acid composition of experimental obscure pufferfish (% TFAs) petfood-grade PBM protein was suggested (Rawles et al, 2006).…”
Section: Ta B L E 8 Effects Of Fishmealmentioning
confidence: 95%
“…One of the main reasons for conducting the digestibility trial after the growth performance is to reduce the stress on the fish, which can affect the growth parameters. Faeces were acquired by stripping from the juveniles after fortnight postprandial utilizing the procedure reported by Hassani et al (2021). After that, collected faeces were frozen‐dried and for apparent digestibility coefficients (ADCs).…”
Section: Methodsmentioning
confidence: 99%